Preparation method of liquid metal composite silicon-based negative electrode material and application of liquid metal composite silicon-based negative electrode material in all-solid-state battery

Silicon-based anode materials were prepared by suspension melting and rapid quenching technology of liquid metal and silicon-based composite materials, which solved the problem of interface contact failure caused by the volume expansion of silicon-based materials in all-solid-state batteries, and realized all-solid-state batteries with high cycle stability and high energy density.

CN120998991APending Publication Date: 2025-11-21XIAN TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511152399.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-18
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

In all-solid-state batteries, the silicon-based anode material suffers from crack formation and solid-solid interface contact failure due to severe volume expansion, which affects cycle stability and energy density.

Method used

Silicon-based anode materials are prepared by combining liquid metal and silicon-based composite materials with suspension melting and rapid quenching technology. A dynamic conductive network is constructed by liquid metal to repair microcracks caused by volume expansion and wet the interface between the electrode and the solid electrolyte, thereby reducing the interface impedance.

Benefits of technology

It significantly improves the cycle stability and energy density of all-solid-state batteries, ensures unobstructed electron/ion transport channels in electrode materials during cycling, and features an efficient and environmentally friendly fabrication process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120998991A_ABST
    Figure CN120998991A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a liquid metal composite silicon-based negative electrode material and application of the liquid metal composite silicon-based negative electrode material in an all-solid-state battery, and relates to the technical field of all-solid-state batteries, and the preparation method specifically comprises the following steps: S1, obtaining a silicon-based composite material compounded by a silicon-based phase and a metal phase by adopting a suspension smelting and rapid quenching technology; s2, mixing a silicon material or a silicon-based composite material with a conductive agent, and obtaining a silicon material-conductive agent powder material or a silicon-based composite material-conductive agent powder material through a sanding technology; and S3, pouring the silicon powder and liquid metal into a dispersing agent, uniformly mixing by adopting a stirring-ultrasonic-stirring method, and drying in a vacuum drying oven to obtain the silicon-based negative electrode material. According to the method, the liquid metal dynamically repairs silicon cracks by utilizing the fluidity in the charging and discharging process, and the connectivity of an internal conductive network is maintained; and by filling an electrode-electrolyte interface gap, the stability of an ion transmission channel is ensured, and the interface impedance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of all-solid-state battery technology, specifically to a method for preparing a liquid metal composite silicon-based anode material and its application in all-solid-state batteries. Background Technology

[0002] With the increasing energy demands from electric vehicles and grid energy storage, the need for energy storage batteries with higher safety, lower cost, higher energy density, and longer cycle life is becoming increasingly prominent. Currently, safety issues and range anxiety are two key obstacles restricting the widespread application of electric vehicles. Compared to all-solid-state batteries, traditional liquid electrolyte batteries have lower energy density and significant shortcomings in safety, energy density, and lifespan, and their performance potential is nearing its limit. As an emerging energy storage technology, all-solid-state batteries, with their advantages of high safety, high energy density, and long lifespan, are not only expected to gain wider market application but will also become an important development direction in the future energy storage field.

[0003] However, the industrialization of all-solid-state batteries still faces severe challenges, with the application bottleneck of silicon-based anode materials being particularly prominent. Silicon, due to its ultra-high theoretical specific capacity (3579 mAh / g), is considered an ideal anode material, but it undergoes a volume expansion of up to 300% during charge and discharge, leading to delamination or cracking at the solid-solid interface between the electrode and the solid electrolyte. This results in a significant increase in interfacial impedance and accelerated capacity decay. In existing technologies, researchers have attempted to mitigate the volume effect through silicon particle nanosizing, carbon coating, or the introduction of polymer buffer layers, but these methods often come at the cost of sacrificing energy density or increasing process complexity. Summary of the Invention

[0004] This invention addresses the aforementioned problems by providing a method for preparing a liquid metal composite silicon-based anode material and its application in all-solid-state batteries. The aim is to solve the problems of crack formation and solid-solid interface contact failure caused by the drastic volume expansion of silicon-based materials, thereby improving the cycle stability and energy density of all-solid-state batteries. The preparation method proposed in this invention is simple and easy to operate and implement.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing a liquid metal composite silicon-based anode material, using silicon material or a silicon-based composite material of silicon-based phase and metal phase as a precursor, and then combining it with liquid metal, specifically including the following steps: S1: A silicon-based composite material combining silicon-based phase and metal phase is obtained by using suspension melting combined with rapid quenching technology; S2: Mix silicon material or silicon-based composite material with a conductive agent, and obtain silicon material-conductive agent powder material or silicon-based composite material-conductive agent powder material through sand milling technology; S3: Pour the above-mentioned silicon material-conductive powder or silicon-based composite material-conductive powder and liquid metal into a dispersant, mix them evenly by stirring-ultrasound-stirring, and then dry them in a vacuum oven to obtain a silicon-based anode material powder sample.

[0006] Furthermore, in step S1, the silicon material is micron-sized silicon powder; the silicon-based phase is a Si-Sn solid solution phase, collectively referred to as the Si-Sn phase; the content of Sn in the Si-Sn phase does not exceed 1 to 30% of the total Si-Sn molar fraction.

[0007] Further, in step S1, the metal phase is any one of (1) Y among rare earth elements; or (2) Bi, a metal element with a melting point less than 1000 degrees Celsius and a boiling point less than 2200 degrees Celsius; or (3) Ni or Ti, a metal element with a melting point greater than 1000 degrees Celsius and a boiling point less than 5000 degrees Celsius; the metal phase accounts for 2% to 20% of the molar fraction of the silicon-based composite material.

[0008] Furthermore, in step S1, the specific method of combining suspension melting with rapid quenching technology is as follows: S11: The mixture of bulk raw materials Si, Sn and metal M is placed in a graphite crucible and vacuum levitation induction melting is performed under an argon atmosphere to obtain a mixed ingot; after cooling, the surface graphite of the mixed ingot is ground off, cleaned with kerosene for 30 minutes, and ultrasonically treated with ethanol for 1 hour; after drying at room temperature, the ingot is placed in a copper crucible and vacuum levitation induction melting is performed three more times under an argon atmosphere to achieve uniformity of composition, thus obtaining a Si-Sn-M composite material ingot composed of silicon-based phase and metal phase. S12: The Si-Sn-M composite material ingot obtained by the above induction melting is mechanically crushed, and a block of appropriate size is placed in a quartz tube. In a vacuum spin quenching furnace, suspension melting is carried out under an argon atmosphere. By gradually increasing the heater power, when the material is completely melted and jumping in the form of flame in the quartz tube, the melt is transferred through a nozzle carrying argon gas flow and sprayed onto a high-speed rotating copper roller. After cooling, the rapid quenching product is collected, which is a silicon-based composite material composed of silicon-based phase and metal phase.

[0009] Furthermore, in step S11, the vacuum degree during vacuum levitation induction melting is 4×10⁻⁶. -3 Pa; In step S12, the vacuum degree of the vacuum rotary quenching furnace is 6.0 × 10⁻⁶. -3 ~3.0×10 -3The pressure inside the furnace is -0.5 MPa, the pressure of the argon gas flow conveying the molten casting in the nozzle is 0.2 MPa, and the rotation speed of the copper roller is 1911 rpm.

[0010] Further, in step S2, the mass ratio of silicon material or silicon-based composite material to conductive agent is 4:1; the conductive agent is (1) any one or more of the following carbon black conductive agents: industrial furnace black, channel black, thermal black, high-temperature graphitized carbon black, and acetylene black; or (2) any one or more of the following graphite conductive agents: artificial graphite and natural graphite; or (3) any one or more of the following fiber and nanotube conductive agents; or (4) any one or more of the following graphene conductive agents; or (5) any one or more of the following biomass carbon.

[0011] Furthermore, in step S2, the sand milling technique involves a rotation speed of 300-8000 rpm, a sand milling time of 10-200 minutes, and the grinding medium being any one or more of ethanol, acetone, or deionized water.

[0012] Further, in step S3, the liquid metal is Ga-In; the mass ratio of silicon material-conductive powder material or silicon-based composite material-conductive powder material to liquid metal is 1:1 to 5:2; the dispersant is any one of anhydrous ethanol and isopropanol; the stirring-ultrasound-stirring is carried out in a water bath or oil bath for 20 to 100 minutes at a temperature of 30 to 60 degrees Celsius, and the ultrasonic time is 20 to 100 minutes; the drying temperature is 60 degrees Celsius.

[0013] This invention constructs a dynamic conductive network within a silicon-based composite material by combining liquid metal with it. The liquid metal, due to its fluidity, acts as a liquid buffer during the lithium insertion / extraction process in silicon, instantly filling microcracks caused by volume expansion and repairing broken electron / ion transport channels. Simultaneously, the liquid metal continuously wets the electrode-solid electrolyte interface, reducing solid-solid interface contact loss and suppressing interfacial impedance growth, thereby significantly improving cycle stability.

[0014] The present invention also provides an application of the silicon-based anode material prepared by the above-described preparation method in an all-solid-state battery.

[0015] The specific application is as follows: using copper foil, which is used in conventional commercial lithium-ion battery anodes, as the current collector, the silicon-based anode material is mixed evenly with the binder (sodium alginate aqueous binder) and conductive agent used in the preparation of conventional lithium-ion battery anodes in a ratio (80:20). The mixing process can be carried out by sand milling, ball milling or other stirring and mixing methods. After being prepared into a slurry, it is coated on the copper current collector, and then rolled, dried and cut to finally prepare the anode.

[0016] All-solid-state battery assembly: All-solid-state battery assembly is carried out in an argon-filled glove box (water content <0.01ppm, oxygen content <0.01ppm). Weigh 50 mg to 200 mg of solid electrolyte powder and place it in a mold. Place it on a tablet press and pre-compress it at a pressure of 200 MPa to 400 MPa for 1 to 10 minutes. Then depressurize and remove it. Place the electrode sheet, lithium sheet and indium sheet on both sides of the electrolyte in sequence. Reassemble the mold and place it on the tablet press again at a pressure of 200 MPa to 400 MPa for 1 to 10 minutes. Then assemble and seal it. Place the mold in an external fixture, put on an insulating PEEK sheet and tighten the nut. Remove it from the glove box. Finally, tighten the nut again with a torque wrench to a torque of 5 Nm to 20 Nm to complete the battery encapsulation.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The preparation of silicon-based anode materials is simple and the synthesis process is efficient and fast; (2) The continuous conductive network constructed by liquid metal ensures that the dynamic transport channels of electrons / ions are unobstructed during the cycling process of the electrode material; (3) The raw materials used are widely available and the chemical reagents used are safe, environmentally friendly and pollution-free, which meets the requirements of green chemistry; (4) Liquid metal dynamically repairs silicon cracks through fluidity and fills the gap between the electrode and electrolyte interface, significantly reducing the interface impedance, maintaining long-term stable solid-solid contact, and possessing excellent electrochemical performance. Attached Figure Description

[0018] Figure 1 This is the XRD pattern of the Si-S-1LM anode material in Example 1; Figure 2 The figures show the cycling performance of the Si-S-1LM anode material in Example 1 at (a) a current density of 1500 mA / g and (b) the first charge-discharge curve at 150 mA / g. Figure 3 This is the XRD pattern of the 5Ti-V-0.5LM material in Example 2; Figure 4 The following are the cycling performance of the 5Ti-V-0.5LM anode material in Example 2 at (a) a current density of 1500 mA / g, and (b) the first charge-discharge curve at 150 mA / g. Figure 5 The XRD pattern of the 5Ni-V-0.5LM material in Example 3 is shown. Figure 6 The following are the cycling performance of the 5Ni-V-0.5LM anode material in Example 3 at (a) a current density of 1500 mA / g, and (b) the first charge-discharge curve at 150 mA / g. Figure 7 The XRD pattern of the 5Bi-S-0.5LM material in Example 4 is shown. Figure 8 The figures are the cycling performance of the 5Bi-S-0.5LM anode material in Example 4 at (a) a current density of 1500 mA / g and (b) the first charge-discharge curve at 150 mA / g. Figure 9 The XRD pattern of the 5Bi-V-0.5LM material in Example 5 is shown. Figure 10 The cycling performance of the 5Bi-V-0.5LM anode material in Example 5 is shown in (a) at a current density of 1500 mA / g and (b) at the first charge-discharge curve of 150 mA / g. Figure 11 This is the XRD pattern of the 5Y-V-0.4LM material in Example 6; Figure 12 The cycling performance of the 5Y-V-0.4LM anode material in Example 6 is shown in (a) at a current density of 1500 mA / g and (b) at the first charge-discharge curve of 150 mA / g. Figure 13 The XRD pattern of the pure Si material after sand milling in Comparative Example 1; Figure 14 The graphs show the cycling performance of the pure Si anode material in Comparative Example 1 at a current density of (a) 1500 mA / g and (b) the first charge-discharge curves at 150 mA / g. Figure 15 Si in Comparative Example 2 90 XRD patterns of Sn5Bi5 materials; Figure 16 Si in Comparative Example 2 90 Cycling performance of Sn5Bi5 anode material at a current density of 150 mA / g, and first charge-discharge curve at 150 mA / g. Figure 17 Si in Comparative Example 3 90 XRD patterns of Sn5Ni5 materials; Figure 18 Si in Comparative Example 3 90 Cyclic performance of Sn5Ni5 anode material at (a) 1500 mA / g current density, (b) initial charge-discharge curve at 150 mA / g. Detailed Implementation

[0019] To make the objectives and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0020] Unless otherwise specified, the instruments, reagents, and materials used in the following embodiments are all conventional instruments, reagents, and materials already available in the prior art and can be obtained through legitimate commercial channels. Unless otherwise specified, the experimental methods and detection methods used in the following embodiments are all conventional experimental methods and detection methods already available in the prior art.

[0021] Example 1 1. Preparation of silicon-based anode materials by compositing liquid metal with silicon materials: S1: Mix the micron-sized silicon powder sample with the conductive agent (SFG-6) (mass ratio 4:1), and then use a sand milling technique (the sand milling medium is anhydrous ethanol, the sand milling speed is 1200 rpm, and the sand milling time is 40 minutes). After the sand milling is completed, collect the sand milling slurry and pass it through a 2000-mesh sieve. After vacuum drying, it is manually ground and passed through a 200-mesh sieve to obtain silicon material-conductive agent powder material. S2: Pour the above silicon material-conductive agent powder and Ga-In liquid metal (mass ratio 1:1) into a dispersant (anhydrous ethanol), then pour it into a small beaker and mix it evenly by stirring-sonication-stirring (water bath, stirring time 30 minutes, temperature 50 degrees Celsius, sonication time 50 minutes). Dry it in a vacuum oven at 60 degrees Celsius to obtain a silicon-based anode material powder sample, denoted as Si-S-1LM.

[0022] Figure 1 The XRD pattern of the sample shows that the composite material contains Si, C, and Ga-In alloy phases. Figure 2 (b) The charge-discharge curves also show a lithium insertion / extraction platform of Ga-In alloy (≈0.6V).

[0023] 2. Preparation of Si-S-1LM composite negative electrode and test cell, and testing of electrode electrochemical performance: Using copper foil as the current collector, the Si-S-1LM anode material is mixed uniformly with the binder (2.9 wt% sodium alginate aqueous binder) and conductive agent used in the preparation of conventional lithium-ion battery anodes in a ratio of 80:20. The mixing process can be carried out by sand milling, ball milling or other stirring mixing methods. After preparing the slurry, it is coated on the copper current collector, air-dried naturally, and then placed in an oven for vacuum drying. The electrode sheet is then compacted by holding the pressure at 20 MPa for 60 seconds to form an electrode sheet. After that, it is punched into a 10 mm diameter disc. After recording the disc mass, it is placed in an oven at 105 degrees Celsius for vacuum drying for 11 hours. After cooling to room temperature, it is transferred to an argon glove box and left to stand for 24 hours before battery assembly.

[0024] The all-solid-state battery assembly was carried out in an argon-filled glove box (water content <0.01ppm, oxygen content <0.01ppm). The weighed solid electrolyte powder was placed in a mold and pre-pressed at 300 MPa for 3 minutes on a tablet press. Then the pressure was released and the mold was removed. Electrode sheets, lithium sheets, and indium sheets were placed on both sides of the electrolyte in sequence. The mold was reassembled and placed on the tablet press again, and pressed at 200 MPa for 1 minute. The mold was then assembled and sealed. The mold was placed in an external fixture, an insulating PEEK sheet was placed on it, and the nut was tightened. The mold was removed from the glove box, and finally the nut was tightened again with a torque wrench to a torque of 10 Nm to complete the battery encapsulation.

[0025] The specific capacity and cycle performance of the electrode were tested using a constant current method on an electrochemical testing instrument, with a voltage window of -0.6 to 0.5 volts. In Example 1, silicon material was used as the anode of the all-solid-state battery, and its cycle performance at a current density of 1500 mA / g was listed as... Figure 2 (a) Its initial reversible capacity was 3024.40 mAh / g, and after 150 cycles, the capacity was maintained at 2096.95 mAh / g, with a capacity retention of 69.34% (Comparative Example 1 had a capacity of 1345.00 mAh / g and a capacity retention of 53.36%). The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 2 (b) Its initial reversible specific capacity is 3949.60 mAh / g, and its initial coulombic efficiency is 79.28%. Compared with Comparative Example 1, the battery has a higher capacity and better cycle performance. The cycle performance test at a current density of 1500 mAh / g was conducted by activating the battery twice at current densities of 150 / 300 / 750 / 1050 mAh / g.

[0026] Example 2 1. Preparation of silicon-based anode materials by combining liquid metal with silicon-based composite materials: S1: Si is obtained by using suspension melting combined with rapid quenching technology. 90 Sn5Ti5 composite material: (1) 100 grams of a sample was weighed in a molar ratio of 90:5:5 for silicon (Si) block (purity greater than 99.9 wt%), tin (Sn) block (purity greater than 99.9 wt%), and titanium (Ti) block (purity greater than 99.9 wt%). The sample was placed in a graphite crucible and placed under an argon atmosphere with a vacuum degree of 4 × 10⁻⁶. -3 The mixture was subjected to vacuum induction melting at -0.25 MPa, with the gas pressure increased to -0.25 MPa and the melting power at 15 kW, to obtain a mixed ingot. After cooling, the surface graphite of the mixed ingot was polished off, cleaned with kerosene for 30 minutes, and ultrasonically treated with ethanol for 1 hour. After drying at room temperature, the ingot was placed in a copper crucible and melted under an argon atmosphere at a vacuum degree of 4 × 10⁻⁶ MPa. -3Under the specified conditions, vacuum suspension induction melting was performed three more times to achieve compositional uniformity, resulting in a Si-Sn-Ti composite ingot composed of silicon-based and metallic phases. (2) Manually crush the Si-Sn composite material ingot obtained by the above induction melting, select appropriately sized pieces and place them in a quartz tube. Adjust the vertical distance between the nozzle of the quartz tube and the copper roller to about 3-5 micrometers, and maintain a vacuum of 4×10 -3 In a vacuum rotary quenching furnace, suspension melting is carried out under an argon atmosphere (at a chamber pressure of -0.5 MPa). By gradually increasing the heater power, when the material is completely melted and jumping in the form of a flame in a quartz tube, the melt is transferred through a nozzle carrying an argon gas flow (at a spray pressure of 0.2 MPa) and sprayed onto a high-speed rotating copper roller (at a speed of 1911 rpm). After cooling, the plate-like rapid quenching product is collected, which is a composite of silicon-based phase and metallic phase Si. 90 Sn5Ti5 composite material; S2: The above Si 90 Sn5Ti5 composite material and conductive agent (VGCF) were mixed at a mass ratio of 4:1 and poured into a sand mill (milling speed 1200 rpm, milling time 40 minutes, grinding media anhydrous ethanol). After milling, the slurry was collected, passed through a 2000-mesh sieve, vacuum dried, and then manually ground through a 200-mesh sieve to obtain Si. 90 Sn5Ti5 composite material - conductive agent powder material; S3: Si 90 Sn5Ti5 composite material - conductive agent powder material and Ga-In liquid metal (mass ratio of 2:1) are poured into a dispersant (isopropanol) and mixed evenly by stirring-ultrasound-stirring (water bath, stirring time of 30 minutes, temperature of 50 degrees Celsius, and ultrasonic time of 50 minutes). After that, it is dried in a vacuum oven at 60 degrees Celsius to obtain a silicon-based anode material powder sample, denoted as 5Ti-V-0.5LM.

[0027] Figure 3 The XRD pattern of this sample shows that the composite material contains Si, Sn, C, and TiSi2 phases. A new TiSi2 phase was formed during the material preparation process, but no Ga-In alloy phase was detected. This may be due to uneven distribution of the composite material during preparation. The powder sample selected for XRD testing contained a relatively small amount of Ga-In alloy. Figure 4 The charge-discharge curves in (b) show a lithium insertion / extraction platform with Ga-In alloy (≈0.6V).

[0028] 2. Preparation of 5Ti-V-0.5LM composite anode sheet and test cell, and testing of electrode electrochemical performance: The negative electrode sheet was prepared and the test battery was assembled using the same method as in Example 1, and its electrochemical performance was tested. In Example 2, the composite material was obtained as the negative electrode for an all-solid-state battery, and its cycling performance at a current density of 1500 mA / g was ranked [missing information]. Figure 4 (a) Its initial reversible capacity is 1624.68 mAh / g, and after 200 cycles, the capacity is retained at 1352.79 mAh / g, with a capacity retention of 83.27%. The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 4 (b) Its first charge reversible specific capacity is 1931.47 mAh / g and its first coulombic efficiency is 69.07%. The cycle performance test at a current density of 1500 mAh / g was first activated twice at current densities of 150 / 300 / 750 / 1050 mAh / g.

[0029] Example 3 1. Using the same method as in Example 2, except that the third-phase metal element titanium is replaced with nickel, a silicon-based anode material is prepared by combining liquid metal with a silicon-based composite material, denoted as 5Ni-V-0.5LM: Figure 5 The XRD pattern of this sample shows that the composite material contains Si, Sn, C, and NiSi2 phases. A new NiSi2 phase was formed during the material preparation process, but no Ga-In alloy phase was detected. This may be due to uneven distribution of the composite material during preparation. The powder sample selected for XRD testing contained a relatively small amount of Ga-In alloy. Figure 6 The charge-discharge curves in (b) show a lithium insertion / extraction platform with Ga-In alloy (≈0.6V).

[0030] 2. Preparation of 5Ni-V-0.5LM composite negative electrode and test cell, and testing of electrode electrochemical performance: The negative electrode sheet was prepared and the test battery was assembled using the same method as in Example 1, and its electrochemical performance was tested. Example 3 obtained the cycling performance of the composite material as an all-solid-state battery negative electrode at a current density of 1500 mA / g. Figure 6 (a) Its initial reversible capacity was 1748.73 mAh / g, and after 200 cycles, the capacity was maintained at 1336.91 mAh / g, with a capacity retention of 76.45% (Comparative Example 3 had a capacity of 761.78 mAh / g and a capacity retention of 59.35%). The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 6(b) Its reversible specific capacity during the first charge is 2227.13 mAh / g, and its initial coulombic efficiency is 70.52%. Compared with Comparative Example 3, the battery has a higher capacity and better cycle performance. The cycle performance test at a current density of 1500 mAh / g was conducted by activating the battery twice at current densities of 150 / 300 / 750 / 1050 mAh / g.

[0031] Example 4 1. Using the same preparation method as in Example 2, except that the third phase metal element titanium is replaced with bismuth metal and the conductive agent is SFG-6. A silicon-based anode material is prepared by combining liquid metal with silicon-based composite material, denoted as 5Bi-S-0.5LM.

[0032] Figure 7 The image shows the XRD pattern of the sample. XRD analysis revealed that the composite material contains Si, Sn, C, and Ga-In alloy phases, but no Bi phase was detected. Similar to Comparative Example 2, this is because the Bi content was low due to volatilization during the material preparation process and was not detected.

[0033] 2. Preparation of 5Bi-S-0.5LM composite negative electrode and test cell, and testing of electrode electrochemical performance: The negative electrode sheet was prepared and the test cell was assembled using the same method as in Example 1, and its electrochemical performance was tested. Example 4 obtained the cycling performance of the composite material as an all-solid-state battery negative electrode at a current density of 1500 mA / g. Figure 8 (a) Its initial reversible capacity was 2509.51 mAh / g, and after 150 cycles, the capacity was maintained at 1894.81 mAh / g, with a capacity retention of 75.51% (Comparative Example 2 had a capacity of 1016.78 mAh / g after 198 cycles, with a capacity retention of 53.05%). The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 8 (b) Its initial reversible specific capacity is 3257.76 mAh / g, and its initial coulombic efficiency is 75.33%. Compared with Comparative Example 2, it has higher capacity and better cycle performance. The cycle performance test at a current density of 1500 mAh / g was conducted by activating it twice at current densities of 150 / 300 / 750 / 1050 mAh / g.

[0034] Example 5 1. Using the same preparation method as in Example 2, except that the third phase metal element titanium is replaced with bismuth metal, and silicon-based anode material is prepared by combining liquid metal with silicon-based composite material, denoted as 5Bi-V-0.5LM.

[0035] Figure 9The XRD pattern of the sample shows that the composite material contains Si, Sn, and C phases, but no Bi phase was detected. This is because the Bi content was low due to volatilization during the material preparation process and was not detected. At the same time, no Ga-In alloy phase was detected, but there were impurity peaks at the corresponding positions in the XRD pattern. This is probably because the Ga-In content of the selected test material was low, which led to its failure to be detected.

[0036] 2. Preparation of 5Bi-V-0.5LM composite negative electrode and test cell, and testing of electrode electrochemical performance: The negative electrode sheet was prepared and the test battery was assembled using the same method as in Example 1, and its electrochemical performance was tested. Example 5 obtained the cycling performance of the composite material as an all-solid-state battery negative electrode at a current density of 1500 mA / g. Figure 10 (a) Its initial reversible capacity is 2192.14 mAh / g, and after 200 cycles, the capacity is retained at 1618.63 mAh / g, with a capacity retention of 73.84%. The initial charge-discharge curve at a current density of 150 mAh / g is shown in Figure 1. Figure 10 (b) Its first charge reversible specific capacity is 2858.49 mAh / g and its first coulombic efficiency is 75.91%. The cycle performance test at a current density of 1500 mAh / g was first activated twice at current densities of 150 / 300 / 750 / 1050 mAh / g.

[0037] Example 6 1. The same preparation method as in Example 2 was used, except that the third phase metal element titanium was replaced with yttrium. The mass ratio of the milled powder material to Ga-In liquid metal was 5:2. Silicon-based anode material was prepared by combining liquid metal with silicon-based composite material, denoted as 5Y-V-0.4LM.

[0038] Figure 11 The XRD pattern of the sample shows that the composite material contains Si, Sn, C, and a new phase, YSi2, indicating the formation of this phase during the material preparation process. However, the Ga-In alloy phase was not detected, likely due to the low Ga-In content of the selected test material. Figure 12 (b) shows a lithium insertion / extraction platform of Ga-In alloy (≈0.6V).

[0039] 2. Preparation of 5Y-V-0.4LM composite negative electrode and test cell, and testing of electrode electrochemical performance: The negative electrode sheet was prepared and the test battery was assembled using the same method as in Example 1, and its electrochemical performance was tested. Example 6 obtained the cycling performance of the composite material as an all-solid-state battery negative electrode at a current density of 1500 mA / g. Figure 12(a) Its initial reversible capacity is 2794.14 mAh / g, and after 200 cycles, the capacity is maintained at 2254.77 mAh / g, with a capacity retention of 80.70%. The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 12 (b) Its first charge reversible specific capacity is 3258.77 mAh / g and its first coulombic efficiency is 77.57%. The cycling performance test at a current density of 1500 mAh / g was first activated twice at current densities of 150 / 300 / 750 / 1050 mAh / g.

[0040] Comparative Example 1 The preparation process is basically the same as in Example 1, except that it is not combined with liquid metal. The raw material is pure silicon (Si) material after sand milling.

[0041] Figure 13 The XRD pattern of the product after sand milling shows that it contains Si and C phases, but no other impurity phases. Test cells were prepared using the same method as in Example 1. Cycling performance at a current density of 1500 mA / g is listed below. Figure 14 (a) Its initial reversible capacity was 2520.63 mAh / g, and after 200 cycles, the capacity remained at 934.63 mAh / g, with a capacity retention of 37.08%. Compared to Example 1, the capacity decay was much faster. The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 14 (b) The initial reversible specific capacity was 3210.06 mAh / g, and the initial coulombic efficiency was 81.37%. This indicates that the pure silicon sample without liquid metal composite exhibits extremely poor cycle stability. Severe volume expansion of Si leads to internal cracks, hindering electron / ion transport and deteriorating interfacial contact. Therefore, this further demonstrates that liquid metal, due to its fluidity, can act as a liquid buffer medium during the silicon lithium insertion / extraction process, repairing microcracks caused by volume expansion, and playing a significant role in improving the electrochemical performance of the sample.

[0042] Comparative Example 2 The preparation process is basically the same as in Example 4, except that it is not combined with liquid metal. The raw material is Si after sand milling. 90 Sn5Bi5 material.

[0043] Figure 15 The XRD pattern of the product after sand milling shows the presence of Si, Sn, and C phases, but no Bi phase was detected. This is because the Bi content in the sample is too low to be detected due to volatilization. Test batteries were prepared using the same method as in Example 4. Cycling performance at a current density of 1500 mA / g is listed below. Figure 16(a) Its initial reversible capacity was 1916.75 mAh / g, and after 198 cycles, the capacity remained at 1016.78 mAh / g, with a capacity retention of 53.05%. Compared with Example 4, the capacity decay was faster. The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 16 (b) Its first-charge reversible specific capacity is 2769.55 mAh / g, and its first-charge coulombic efficiency is 77.69%. This indicates that the combination of liquid metal and ternary system materials can also effectively improve the electrochemical performance of the materials.

[0044] Comparative Example 3 The preparation process is basically the same as in Example 3, except that it is not combined with liquid metal. The raw material is Si after sand milling. 90 Sn5Ni5 material.

[0045] Figure 17 The XRD pattern of the product after sand milling shows the presence of Si, Sn, C, and NiSi2 phases. Test cells were prepared using the same method as in Example 3. Cycling performance at a current density of 1500 mA / g is listed below. Figure 18 (a) Its initial reversible capacity was 1283.62 mAh / g, and after 200 cycles, the capacity remained at 761.78 mAh / g, with a capacity retention of 59.35%. Compared with Example 3, the capacity decay was faster. The initial charge-discharge curve at a current density of 150 mAh / g is shown below. Figure 18 (b) Its first-charge reversible specific capacity is 2134.06 mAh / g, and its first-charge coulombic efficiency is 72.60%. This indicates that the combination of liquid metal and ternary system materials can also effectively improve the electrochemical performance of the materials.

[0046] In addition to the above embodiments: In some other embodiments of the present invention, the vacuum degree of the vacuum quenching furnace in step S1 is 6.0 × 10⁻⁶. -3 Pa or 3.0×10 -3 Pa.

[0047] In some other embodiments of the present invention, the conductive agent in step S2 is (1) any one or more of the following carbon black conductive agents: industrial furnace black, channel black, thermal black, high-temperature graphitized carbon black, and acetylene black; or (2) any one or more of the following graphite conductive agents: artificial graphite and natural graphite; or (3) any one or more of the following fiber and nanotube conductive agents; or (4) any one or more of the following graphene conductive agents; or (5) any one or more of the following biomass carbon.

[0048] In some other embodiments of the present invention, the grinding speed in step S2 is 300 rpm, the time is 200 minutes, and the grinding medium is acetone.

[0049] In some other embodiments of the present invention, the grinding speed in step S2 is 8000 rpm, the time is 10 minutes, and the grinding medium is deionized water.

[0050] In some other embodiments of the present invention, in step S3, the stirring-ultrasounding-stirring is carried out in an oil bath for 20 minutes at a temperature of 60 degrees Celsius, and the ultrasonication time is 20 minutes.

[0051] In some other embodiments of the present invention, in step S3, the stirring-ultrasounding-stirring is carried out in an oil bath for 100 minutes at a temperature of 30 degrees Celsius, and the ultrasonication time is 100 minutes.

[0052] In some other embodiments of the invention, the pre-pressure is 50 MPa for 20 minutes; the final pressure is 400 MPa for 5 minutes; and the torque of the torque wrench is 5 Nm.

[0053] In some other embodiments of the invention, the pre-pressure is 500 MPa for 1 minute; the final pressure is 300 MPa for 10 minutes; and the torque of the torque wrench is 20 Nm.

[0054] All solid-state batteries assembled from silicon-based anode materials prepared in the above examples exhibit excellent electrochemical performance.

[0055] In summary, this embodiment combines liquid metal with silicon-based materials (the precursors being micron-sized silicon powder and silicon-based composite materials prepared by suspension melting-rapid quenching), mixes them with a conductive agent after sand milling, adds liquid metal in a specific ratio, and achieves uniform dispersion through a stirring-ultrasound-stirring process, finally obtaining composite powder through vacuum drying. During charge and discharge, the liquid metal dynamically repairs silicon cracks using its fluidity, maintaining the connectivity of the internal conductive network; simultaneously, it fills the gaps at the electrode-electrolyte interface, ensuring stable ion transport channels and reducing interfacial impedance. Experimental results show that this negative electrode enables the all-solid-state battery to achieve higher capacity retention and better cycle performance after 200 cycles at 1500 mAh / g compared to the comparative example, providing a quantitative verification scheme for the industrialization of high-energy-density, long-cycle-life all-solid-state batteries.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a liquid metal composite silicon-based anode material, characterized in that: Using silicon materials or silicon-based composite materials combining silicon-based and metal phases as precursors, and then combining them with liquid metal, the specific steps include: S1: A silicon-based composite material combining silicon-based phase and metal phase is obtained by using suspension melting combined with rapid quenching technology; S2: Mix silicon material or silicon-based composite material with a conductive agent, and obtain silicon material-conductive agent powder material or silicon-based composite material-conductive agent powder material through sand milling technology; S3: The above-mentioned silicon material-conductive powder material or silicon-based composite material-conductive powder material and liquid metal are poured into the dispersant, mixed evenly by stirring-ultrasound-stirring method, and then dried in a vacuum oven to obtain silicon-based anode material.

2. The method for preparing a liquid metal composite silicon-based anode material according to claim 1, characterized in that: In step S1, the silicon material is micron-sized silicon powder; the silicon-based phase is a Si-Sn solid solution phase, collectively referred to as the Si-Sn phase; the content of Sn in the Si-Sn phase does not exceed 1 to 30% of the total Si-Sn molar fraction.

3. The method for preparing a liquid metal composite silicon-based anode material according to claim 1, characterized in that: In step S1, the metal phase is any one of (1) Y, a rare earth element; or (2) Bi, a metal element with a melting point less than 1000 degrees Celsius and a boiling point less than 2200 degrees Celsius; or (3) Ni or Ti, a metal element with a melting point greater than 1000 degrees Celsius and a boiling point less than 5000 degrees Celsius; the metal phase accounts for 2% to 20% of the molar fraction of the silicon-based composite material.

4. The method for preparing a liquid metal composite silicon-based anode material according to claim 1, characterized in that: In step S1, the specific method of combining suspension melting with rapid quenching technology is as follows: S11: The mixture of bulk raw materials Si, Sn and metal M is placed in a graphite crucible and vacuum levitation induction melting is performed under an argon atmosphere to obtain a mixed ingot; after cooling, the surface graphite of the mixed ingot is ground off, cleaned with kerosene for 30 minutes, and ultrasonically treated with ethanol for 1 hour; after drying at room temperature, the ingot is placed in a copper crucible and vacuum levitation induction melting is performed three more times under an argon atmosphere to achieve uniformity of composition, thus obtaining a Si-Sn-M composite material ingot composed of silicon-based phase and metal phase. S12: The Si-Sn-M composite material ingot obtained by the above induction melting is mechanically crushed, and a block of appropriate size is placed in a quartz tube. In a vacuum spin quenching furnace, suspension melting is carried out under an argon atmosphere. By gradually increasing the heater power, when the material is completely melted and jumping in the form of flame in the quartz tube, the melt is transferred through a nozzle carrying argon gas flow and sprayed onto a high-speed rotating copper roller. After cooling, the rapid quenching product is collected, which is a silicon-based composite material composed of silicon-based phase and metal phase.

5. The method for preparing a liquid metal composite silicon-based anode material according to claim 4, characterized in that: In step S11, the vacuum degree during vacuum levitation induction melting is 4×10⁻⁶. -3 Pa; In step S12, the vacuum degree of the vacuum rotary quenching furnace is 6.0 × 10⁻⁶. -3 ~3.0×10 -3 The pressure inside the furnace is -0.5 MPa, the pressure of the argon gas flow conveying the molten casting in the nozzle is 0.2 MPa, and the rotation speed of the copper roller is 1911 rpm.

6. The method for preparing a liquid metal composite silicon-based anode material according to claim 1, characterized in that: In step S2, the mass ratio of silicon material or silicon-based composite material to conductive agent is 4:1; the conductive agent is (1) any one or more of the following carbon black conductive agents: industrial furnace black, channel black, thermal black, high-temperature graphitized carbon black, and acetylene black; or (2) any one or more of the following graphite conductive agents: artificial graphite and natural graphite; or (3) any one or more of the following fiber and nanotube conductive agents; or (4) any one or more of the following graphene conductive agents; or (5) any one or more of the following biomass carbon.

7. The method for preparing a liquid metal composite silicon-based anode material according to claim 1, characterized in that: In step S2, the sand milling technology is as follows: the rotation speed is 300~8000 rpm, the sand milling time is 10~200 minutes, and the grinding medium is any one or more of ethanol, acetone or deionized water.

8. The method for preparing a liquid metal composite silicon-based anode material according to claim 1, characterized in that: In step S3, the liquid metal is Ga-In; the mass ratio of silicon material-conductive powder material or silicon-based composite material-conductive powder material to liquid metal is 1:1 to 5:2; the dispersant is any one of anhydrous ethanol and isopropanol; the stirring-ultrasound-stirring is carried out in a water bath or oil bath for 20 to 100 minutes at a temperature of 30 to 60 degrees Celsius, and the ultrasonic time is 20 to 100 minutes; the drying temperature is 60 degrees Celsius.

9. The application of the silicon-based anode material prepared by any one of the preparation methods described in claims 1-8 in all-solid-state batteries.

Citation Information

Cited By

  • Preparation method of silicon-based negative plate and battery

    CN121839582A